Impact of Learning Content in Youtube on the Attitude of Information Technology Education Students - Saputra, Bayu; Riyanda, Afif Rahman; Surawan, Ghea Chandra (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2020)
This research aims to determine the impact of YouTube learning content on the attitudes of students of Information Technology Education in the Teaching and Education Faculty, University of Lampung, (PTI, FKIP Unila). This study uses a simple correlational method, consisting of variable X content on YouTube and Y student attitudes, as well as the strength and direction of both. The results of the study of PTI FKIP Unila student attitudes showed a strong relationship with the moment product value of 0.62, while attitude had a large influence with a determinant value of 37.0%. So that the overall value obtained is strong and a large positive influence Keywords: Learning Content, YouTube, Students’ AttituteDOI : http://dx.doi.org/10.23960/jpvti.v2.i1.202004